Modeling and simulation of a pervaporator coupled to a simultaneous saccharification-fermentation process for the ethanol production (2015)
Process integration is now days considered a viable option for reducing ethanol production costs from biomass. Both experimental and simulation results have shown the benefits of coupling saccharification and fermentation as well as fermentation and pervaporation. However, the integration of simultaneous saccharification-fermentation with membrane-based in-situ removal of ethanol, which would allow reaching the benefits of this approach, has not been reported yet. This work aims to obtain the modelling and simulation’s results in the production of ethanol, from cassava starch by simultaneous saccharification and fermentation, coupled with the membranes separation, based on Silicalite PDMS, and PDMS-Silicalite.A combined solution-diffusion mechanism and adsorption-diffusion mechanism was used for modelling the PDMS membrane where as the Maxwell-Stefan multi-component mass-transfer equations were used for modelling the silicalite membrane..A simultaneous-saccharification and fermentation process was modelled, using a multi-chain model (Michaelis-Menten) coupled with the Monod model. The maximum deviation found in the adjusted SSF model to the reported experimental data, as well as the values for PDMS and silicalite membrane models, is in the 3% range. The integrated model was used to predict the ethanol concentration during the simultaneous saccharification-fermentation process.